Hidden violence is silent rape: sexual and gender-based violence in refugees, asylum seekers and undocumented migrants in Belgium and the Netherlands - Keygnaert, Ines (Taylor & Francis, 2012)
Although women, young people and refugees are vulnerable to sexual and gender-based violence (SGBV) worldwide, little evidence exists concerning SGBV against refugees in Europe. Using community-based participatory research, 223 in-depth interviews were conducted with refugees, asylum seekers and undocumented migrants in Belgium and the Netherlands. Responses were analysed using framework analysis. The majority of the respondents were either personally victimised or knew of a close peer being victimised since their arrival in the European Union. A total of 332 experiences of SGBV were reported, mostly afflicted on them by (ex-)partners or asylum professionals. More than half of the reported violent experiences comprised sexual violence, including rape and sexual exploitation. Results suggest that refugees, asylum seekers and undocumented migrants in Belgium and the Netherlands are extremely vulnerable to violence and, specifically, to sexual violence. Future SGBV preventive measures should consist of rights-based, desirable and participatory interventions, focusing on several socio-ecological levels concurrently.